A fiber-optic long-base deformometer for a system for monitoring rocks on the sides of quarries - Mekhtiyev, Ali D.; Yurchenko, Alexey V.; Kalytka, V. А.; Neshina, Elena G.; Alkina, Aliya D.; Madi, Perizat Sh (Technical physics letters)
A fiber-optic long-base deformometer has been developed, which can be used in systems for monitoring rocks on the sides of quarries. The proposed deformometer is based on the use of a method for monitoring additional losses of a light wave propagating in an optical fiber. The fiber-optic sensor (FOS) has a sufficiently high linearity and stability of the output signal, and is also not subject to the negative occurrence of feeding characteristic of the FOS created on the basis of the Mach−Zhender interferometer with fluctuations in external temperature and the appearance of false signals about the displacement of rocks.